La mise au jour d’un contrat réflexif comme régulateur de démarches de recherche participative : le cas d'une recherche-action et d'une recherche collaborative - Nadine Bednarz; Serge Desgagné; Jean-François Maheux; Lorraine Savoie Zajc (Recherches en Éducation)
Participative research promotes a view of research as conducted with those directly concerned by the objects investigated. Hence, it requires a re-thinking of the relationships between researchers (traditionally conceived as the experts) and practitioners (as ‘end-users’). To better understand these new dynamics in educational research, we investigated the interactions taking place between researchers and practitioners in two sites of research: one of action research and one of collaborative research. Our analysis, based on the concept of implicit reflexive contract, helps to understand how researchers and practitioners contribute to one another in the very course of the researching, and in ways that are specific to the adopted research design.